Antenna array placement on limited bound for isotropic and optimal direction‐of‐arrival estimation. Issue 3 (1st May 2018) - Ghani, Armin; Keyvani, Firooz; Sedighy, Seyed Hassan
Abstract : An optimal placement for planar antenna array elements is proposed to achieve a precise direction of arrival (DOA) estimation on a limited bound. For this purpose, the Cramer–Rao lower bound is chosen as a suitable and useful criterion. In order to have an accurate isotropic DOA estimation, the placement of the antenna elements in the array configuration is achieved by using the invasive weed optimisation algorithm. Moreover, the optimisation results show higher efficiency compared with the similar uniform circular array. It is proved that the optimised arrays are ambiguity free, also.